Kinematic analysis of tandem gait on a sine wave walkway - Kawakami, Shingo (J Phys Ther Sci, 2016)
[Purpose] The purpose of this study was to ascertain the kinematic characteristics on a horizontal plane, including knee joint rotation, when walking with a tandem gait on a sine wave walkway. [Subjects and Methods] Eighteen healthy adults were enrolled as subjects in this study. They walked with a tandem gait on a sine wave walkway. A three-dimensional motion analysis system was used to record data and calculate the trunk, hip joint, and knee joint rotation angles. [Results] The rotation angle ranges for the trunk, hip joint, and knee joint were 23.3°, 53.3°, and 47.3°, respectively. The trunk generally rotated towards the direction of movement, and when turning left using the left leg as the pivot, the hip joint was internally rotated and the knee joint was externally rotated. In contrast, when making a directional change to the right using the left leg as the pivot, the hip joint was externally rotated and the knee joint was internally rotated. [Conclusion] Through tandem gait analysis on a sine wave walkway, knee joint rotation was found to be important in changes of direction.